Coupled modeling of combustion and hydrodynamics for a supercritical CO2 boiler. (October 2018) - Wang, Feng-jun; Su, Hong-liang; Chen, Tang; Yu, Qiang; Huang, Yin; Zhang, Yan-jun; Shen, Tao
Highlights: Hydrodynamic model of supercritical CO2 (S-CO2 ) is coupled with combustion simulation. Tube outside surface temperature is obtained. Mass flow rate of fluid in each tube is calculated. Abstract: A one-dimensional hydrodynamic model of supercritical CO2 (S-CO2 ) coupled with computational fluid dynamics (CFD) simulation of gas combustion is developed. The heat exchangers are introduced into the CFD simulation as energy/momentum absorption sources. Complex tube structures can be built with the aid of AutoCAD, and therefore the simulation could give detailed information of heat exchangers. Numerical simulation is performed for a 5MWe gas-fired S-CO2 test boiler. The calculation results are validated by the thermodynamic design data. Tube outside surface temperature, as well as S-CO2 temperature distributions are obtained.